An easy plane R2Fe for high frequency soft magnetic composite applications 17 C x Rare earth alloy soft magnetic powder and method of making same

CN122991793APending Publication Date: 2026-10-27LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611218676.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

首先,R2Fe17化合物的居里温度相对较低,限制了其在高功率密度场景下的热稳定性

Benefits of technology

(1)本发明将R2Fe17基材料由传统块体磁性材料拓展至金属软磁复合材料用软磁粉末领域,构建了一种不同于FeSi、FeSiAl、FeNi及非晶、纳米晶材料的新型软磁粉末体系。所得R2Fe17Cx软磁粉末具有Th2Ni17型主相结构和易面磁晶各向异性,可作为软磁复合材料的磁性相应用于高频功率电感等器件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991793A_ABST
    Figure CN122991793A_ABST
Patent Text Reader

Abstract

The application discloses an easy-to-face R2Fe 17 C x The application discloses a rare earth alloy soft magnetic powder and a preparation method thereof, and belongs to the technical field of magnetic materials. 17 C x The chemical formula of the soft magnetic powder is R2Fe 17 x is 0.5-3.2, and the soft magnetic powder has a Th2Ni 17 type main phase structure and easy-to-face magnetic crystal anisotropy. The application introduces gap carbon by using Fe-C pre-alloy as a carbon source, combines with rare earth excess compensation, homogenization annealing and ball milling or gas atomization powdering process, and obtains the R2Fe x C soft magnetic powder with high saturation magnetization, low coercivity and relatively high Curie temperature. The soft magnetic powder can be further compounded with a SiO2 insulation coating layer or an organic resin binder to prepare a high-frequency soft magnetic composite material, and the composite material has a stable complex permeability response in a frequency range of 1-100 MHz. The soft magnetic powder breaks the high-frequency performance bottleneck of traditional axial magnetization soft magnetic materials limited by the Snoek limit, and can be used for preparing high-frequency power inductors, high-frequency magnetic powder cores and other high-frequency soft magnetic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnetic materials technology, specifically relating to an easy-surface R2Fe for high-frequency soft magnetic composite materials and magnetic powder core applications. 17 C x Rare earth alloy soft magnetic powder, composite material and preparation method thereof (R is one of Y, Nd and Pr). Background Technology

[0002] Soft magnetic composites (SMCs) are a class of magnetic materials prepared by pressing and molding soft magnetic metal powder as the magnetic phase and insulating material as the coating phase. They possess advantages such as high resistivity and low eddy current loss, and are widely used in high-frequency inductors, transformers, and sensors. With the continuous development of power electronic devices towards higher frequencies, miniaturization, and higher power density, wide-bandgap semiconductors, represented by SiC and GaN, have raised the operating frequency of power electronic devices to MHz and even GHz, placing higher demands on soft magnetic powder materials. The rapid application of next-generation power semiconductors has shifted the performance bottleneck of modern power electronics from active devices to passive magnetic devices. Soft magnetic composites have become a highly anticipated candidate material due to their potential for high saturation magnetization and low-loss high-frequency operation. This requires not only high saturation magnetization and low coercivity, but also high permeability, low core loss, and good thermal stability under high-frequency conditions.

[0003] Currently, the soft magnetic powders of metals used in high-frequency power inductors can be mainly divided into two categories.

[0004] The first category consists of traditional cubic soft magnetic materials such as FeSi, FeSiAl, FeNi, and FeNiMo. These materials all belong to the cubic crystal system, and magnetization preferentially occurs along the easy magnetization axis (easy axis). For these axially magnetized materials, their high-frequency magnetic properties are strictly limited by the Snoek limit—the product of the natural resonant frequency and the initial permeability of the magnetic material is a constant and proportional to its saturation magnetization. This means that, under a given saturation magnetization, there is an inverse relationship between permeability and cutoff frequency. As the operating frequency increases, the permeability decreases rapidly, making it difficult to meet the development requirements of higher frequency power inductors. In other words, the rapid decay of permeability in traditional easy-axis metallic soft magnetic materials under high-frequency conditions has become a core bottleneck restricting their further application.

[0005] The second category consists of Fe-based amorphous and nanocrystalline soft magnetic materials. These materials exhibit low coercivity and good overall soft magnetic properties, but they are essentially still axially magnetized systems and are similarly limited by the Snoek limit. Furthermore, their fabrication process is complex, requiring stringent heat treatment procedures, resulting in relatively high manufacturing costs, which limits their further application in the field of high-frequency power inductors.

[0006] In addition to the two types of materials mentioned above, R2Fe 17 (R represents a rare earth element) Rare earth-iron intermetallic compounds have attracted attention due to their unique magnetocrystalline anisotropy. Studies have shown that R₂Fe 17 The compound exhibits easy-plane magnetocrystalline anisotropy at room temperature, meaning magnetization preferentially occurs within the basal plane (easy-magnetizing plane) of the crystal, rather than along a specific crystal axis. This easy-plane anisotropy allows it to overcome the traditional Snoek limit—according to the bi-anisotropy model, easy-plane magnetized materials can achieve higher cutoff frequencies at a given permeability. However, R2Fe 17 Although research on matrix materials as bulk magnetic materials has been accumulated for many years, their application exploration in the field of soft magnetic composite materials is still very limited.

[0007] R2Fe 17 Expanding the application of R2Fe base materials to soft magnetic powders for SMC (Silicone Magnetite) faces several key technological challenges. Firstly, R2Fe... 17 The relatively low Curie temperature of the compound limits its thermal stability in high-power-density applications. Secondly, there is a lack of mature processes for efficiently preparing bulk materials into soft magnetic powders with suitable particle size, maintaining good surface anisotropy, and low coercivity. Thirdly, while the introduction of interstitial atoms such as carbon and nitrogen has been shown to improve R2Fe... 17 The magnetic properties of the base material are important, but existing gap introduction methods (such as heat treatment in a methane atmosphere) have problems such as difficulty in accurately controlling carbon content and poor composition uniformity.

[0008] To address the above problems, this invention reports an R2Fe 17 C x This is a soft magnetic powder material made of metal. Through reasonable material composition design and preparation process control, the Curie temperature of the material can be increased while maintaining high saturation magnetization and low coercivity, providing a new soft magnetic powder option for high-frequency power inductors. Summary of the Invention

[0009] Addressing the limitations imposed by the Snoek limit on existing cubic soft magnetic materials and Fe-based amorphous and nanocrystalline materials, the rapid decrease in high-frequency permeability with increasing frequency, and the challenges posed by R2Fe... 17To address the problems of low Curie temperature of base materials and the lack of soft magnetic powder preparation processes suitable for SMC fields, this invention provides an easy-surface R2Fe for high-frequency soft magnetic composite materials or magnetic powder cores. 17 C x Rare earth alloy soft magnetic powder, composite material and preparation method thereof.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: First, this invention provides an easy-surface R2Fe for high-frequency soft magnetic composite materials or magnetic powder cores. 17 C x Rare earth alloy soft magnetic powder, wherein R is any one of Y, Nd, or Pr, and x is 0.5~3.2; the soft magnetic powder has Th2Ni 17 It has a main phase structure and exhibits easy-faceted magnetocrystalline anisotropy.

[0011] Preferably, x is 1.6 to 2.2. When the carbon content is within this range, the material has both high saturation magnetization and low coercivity, resulting in superior overall soft magnetic properties.

[0012] Preferably, R is Y.

[0013] Secondly, the present invention also provides a high-frequency soft magnetic composite material, comprising a magnetic phase and an insulating coating layer covering the surface of the magnetic phase, wherein the magnetic phase is the aforementioned soft magnetic powder.

[0014] Preferably, the insulating coating layer is a SiO2 insulating coating layer or an organic resin adhesive layer; the high-frequency soft magnetic composite material has a stable complex permeability response in the frequency range of 1~100MHz. The organic resin adhesive layer is preferably a polyurethane resin adhesive layer.

[0015] Furthermore, the present invention also provides a method for preparing the above-mentioned soft magnetic powder, comprising the following steps: (1) Raw material preparation: according to the chemical formula R2Fe 17 C x The ingredients are prepared by using Fe-C pre-alloying as a carbon source to introduce carbon elements, with rare earth elements in excess of 10% to 25%. (2) Alloy smelting: The prepared raw materials are smelted under a protective atmosphere, and the smelting is repeated no less than 3 times to obtain R2Fe. 17 C x Alloy ingots; (3) Homogenization annealing: The obtained ingot is annealed at 1000~1050℃ and then cooled; (4) Powder preparation: The annealed alloy is crushed and ball-milled using a planetary ball mill with a ball-to-material ratio of 15:1 to 25:1 and a ball-milling time of 0.5 to 2 hours to obtain the soft magnetic powder.

[0016] Preferably, the excess proportion of rare earth elements is 18%. Using this excess proportion can effectively compensate for the compositional deviation caused by rare earth volatilization during the smelting process and improve the purity of the main phase.

[0017] Preferably, the annealing temperature is 1050℃. Annealing at this temperature promotes element diffusion and complete reaction, resulting in stable Th2Ni. 17 Type principal phase structure Preferably, the ball milling speed is 140 r / min; at this speed, ball milling can obtain soft magnetic powder with uniform particle size and low coercivity. Alternatively, in step (4), vacuum atomization process can be used instead of ball milling process to prepare spherical soft magnetic powder.

[0018] Finally, the present invention also provides the application of the above-mentioned soft magnetic powder in the preparation of high-frequency power inductors, high-frequency magnetic powder cores or high-frequency soft magnetic devices.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses R2Fe 17 The base material has been expanded from traditional bulk magnetic materials to the field of soft magnetic powders for metal soft magnetic composite materials, constructing a novel soft magnetic powder system different from FeSi, FeSiAl, FeNi, and amorphous and nanocrystalline materials. The resulting R2Fe... 17 C x Soft magnetic powder with Th2Ni 17 The main phase structure and easy-plane magnetocrystalline anisotropy can be used as the magnetic response of soft magnetic composite materials for devices such as high-frequency power inductors.

[0020] (2) This invention employs an interstitial carbon control strategy to maintain Th2Ni 17 While maintaining a stable main phase structure, the saturation magnetization and Curie temperature of the material were increased, while keeping the coercivity low. This is due to the R2Fe... 17 C x Magnetization preferentially occurs within the easily magnetizable plane of the crystal, unlike traditional cubic axially magnetized materials. It has the potential to maintain high permeability under high-frequency conditions and is expected to break through the high-frequency performance bottleneck of traditional iron-based soft magnetic alloys limited by the Snoek limit.

[0021] (3) This invention uses Fe-C pre-alloying as the carbon source, and combines rare earth compensation, homogenization annealing, and ball milling processes to improve the carbon element introduction efficiency, main phase purity, and microstructure uniformity. By controlling the rare earth excess ratio to 10%~25%, the annealing temperature to 1000~1050℃, and the ball milling speed to 140r / min, a set of methods suitable for R2Fe was established. 17 C x A stable process route for the preparation of soft magnetic powder.

[0022] (4) The interstitial carbon regulation method proposed in this invention is applicable to various R2Fe such as Y, Nd, and Pr. 17 The resulting R2Fe base material system exhibits good system universality. 17 C x Soft magnetic powder has high saturation magnetization, low coercivity and high Curie temperature, and can be used in high-frequency power inductors and other high-frequency soft magnetic devices.

[0023] (5) The soft magnetic powder obtained in this invention can be further combined with a SiO2 insulating coating layer or an organic resin binder to prepare a high-frequency soft magnetic composite material. This composite material exhibits a stable complex permeability response in the frequency range of 1–100 MHz. This result demonstrates that the R2Fe obtained in this invention… 17 C x Soft magnetic powder has practical feasibility in constructing high-frequency soft magnetic composite materials and magnetic powder cores. Attached Figure Description

[0024] Figure 1 R2Fe of the present invention 17 C x A schematic diagram of the preparation process of soft magnetic powder materials.

[0025] Figure 2 (a) Y2Fe obtained in Example 1 17 C 1.6 X-ray diffraction patterns of the sample before and after orientation; Figure 2 (b) Y2Fe obtained in Example 1 17 C 1.6 Initial magnetization curves in the in-plane and out-of-plane directions of the sample.

[0026] Figure 3 (a) R2Fe with different carbon contents 17 C x X-ray diffraction pattern of the sample; Figure 3 (b) R2Fe with different carbon contents 17 C x Graph showing the relationship between sample lattice parameter a and carbon content; Figure 3 (c) R2Fe with different carbon contents 17 C x The relationship between the sample lattice parameter c and carbon content.

[0027] Figure 4 For different carbon contents of R2Fe 17 C x Results of Curie temperature variation of the sample.

[0028] Figure 5 For R2Fe with different carbon contents 17 Cx The hysteresis loop of the sample.

[0029] Figure 6 (a) Different rare earth elements R2Fe 17 C x X-ray diffraction pattern of the sample; Figure 6 (b) represents different rare earth elements R2Fe 17 C x The hysteresis loop of the sample.

[0030] Figure 7 (a) X-ray diffraction patterns of samples with different rare earth excess ratios; Figure 7 (b) Hysteresis loops for samples with different rare earth excess ratios.

[0031] Figure 8 Pr2Fe at different annealing temperatures 17 C 1.6 X-ray diffraction pattern of the sample.

[0032] Figure 9 (a) Scanning electron microscope images of soft magnetic powders obtained at different ball milling speeds; Figure 9 (b) shows the hysteresis loops of soft magnetic powders obtained at different ball milling speeds.

[0033] Figure 10 (a) is a scanning electron microscope image of the spherical powder after atomization; Figure 10 (b) is the hysteresis loop of the corresponding powder.

[0034] Figure 11 The uncoated R2Fe obtained in Example 8 17 C X The high-frequency magnetic properties test results of the polyurethane soft magnetic composite sample, among which... Figure 11 (a) shows the curves of the real part μ' and imaginary part μ'' of the complex permeability as a function of frequency for samples with different carbon contents. Figure 11 (b) represents the magnetic loss factor tanδ for the corresponding sample. μ Curve showing variation with frequency.

[0035] Figure 12 SiO2 coating R2Fe 17 C X The high-frequency magnetic properties test results of the resin-based soft magnetic composite sample, among which... Figure 12 (a) shows the curves of the real part μ' and imaginary part μ'' of the complex permeability of the sample as a function of frequency. Figure 12 (b) represents the magnetic loss factor tanδ for the corresponding sample. μ Curve showing variation with frequency. Figure 12 (c) R2Fe coated with SiO2 17 CX / Loss test results of resin-based soft magnetic composite samples. Detailed Implementation

[0036] The technical solution of the present invention will be further described below through specific embodiments. These embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0037] Example 1 According to the chemical formula Y₂Fe 17 C 1.6 The raw materials were prepared with a 18% excess of Y and carbon introduced via Fe-C pre-alloying. High-purity Y ingots, high-purity Fe ingots, and the Fe-C alloy (5wt% C) were weighed and placed in a medium-frequency induction melting furnace for melting under a high-purity argon protective atmosphere. The amount of high-purity Fe ingots added was adjusted based on the amount of iron introduced from the Fe-C pre-alloy to maintain a Fe:C molar ratio of 17:1.6. After melting, the resulting alloy was repeated three times to ensure uniform distribution of elements, yielding Y₂Fe. 17 C 1.6 Alloy ingots.

[0038] The resulting ingot was encapsulated in a vacuum-sealed quartz tube and annealed at 1050°C for 7 days, followed by furnace cooling to room temperature. The annealed block sample was mechanically crushed and then powdered using a planetary ball mill with a ball-to-material ratio of 20:1, a milling speed of 140 r / min, and a milling time of 1 h, to obtain the sample of Example 1.

[0039] Example 2 Following the preparation process of Example 1, the carbon content was varied to prepare a product with the chemical composition Y2Fe. 17 C 0、 Y2Fe 17 C 0.5 Y2Fe 17 C 1.0 Y2Fe 17 C 2.2 and Y2Fe 17 C 3.2 The sample of Example 2 was obtained by keeping all other process conditions the same as in Example 1.

[0040] Example 3 Following the preparation process of Example 1, Nd and Pr were used to replace Y as rare earth elements, and R2Fe was prepared in the same stoichiometric ratio. 17 C x (R represents Nd and Pr) alloys, with all other process parameters remaining the same as in Example 1, to obtain the sample of Example 3.

[0041] Example 4 Following the preparation process of Example 1, rare earth elements were added in excess amounts of 10%, 15%, 18%, and 25%, respectively, while keeping other process parameters consistent, in order to study the effect of the excess rare earth ratio on the phase composition and magnetic properties of the material, and thus the sample of Example 4 was obtained.

[0042] Example 5 To study the effect of annealing temperature on R2Fe 17 C x The influence of material phase formation, taking Pr2Fe 17 C 1.6 Using this as the research object, Pr2Fe was prepared by completing the raw material preparation and induction melting according to the method described in Example 1. 17 C 1.6 Alloy ingots were prepared and encapsulated in vacuum-sealed quartz tubes. They were then annealed at 1000℃ and 1050℃ for 7 days, followed by furnace cooling to room temperature. After annealing, X-ray diffraction was performed on the samples to compare the effects of different annealing temperatures on the phase composition and main phase formation of the material.

[0043] Example 6 Following the preparation process of Example 1, ball milling was performed at 100 r / min, 140 r / min, and 200 r / min, respectively, with a ball-to-material ratio of 20:1 and a ball milling time of 1 h. All other process parameters remained the same to study the effect of ball milling on powder particle size and magnetic properties, thus obtaining the sample of Example 6.

[0044] Example 7 R2Fe prepared using Example 1 17 C x Alloy ingots are used as master alloys, and vacuum atomization is used to produce powder.

[0045] The master alloy is remelted and atomized under a protective atmosphere using a high-pressure inert gas (Ar or N2). This causes the molten metal stream to break up and solidify rapidly under the action of a high-speed gas flow, resulting in near-spherical R2Fe. 17 C x Alloy powder. Subsequently, a sieving process was used to obtain spherical powders with different particle size ranges.

[0046] After annealing, the obtained spherical powder can be further coated with insulation and pressed into shape to prepare soft magnetic composite material magnetic powder cores.

[0047] Example 8 R2Fe was prepared under the ball milling condition of 140 r / min as described in Example 6. 17 C xSoft magnetic powder was used as a magnetic filler, and it was composited with polyurethane and the high-frequency complex permeability was tested.

[0048] R2Fe after ball milling 17 C x Soft magnetic powder and polyurethane resin are mixed at a mass ratio of 96:4, thoroughly stirred and dispersed, then cast into molds and cured at room temperature or under heating conditions to obtain R2Fe. 17 C x / Polyurethane soft magnetic composite material. Subsequently, an impedance analyzer was used to test the complex permeability of the composite sample in the frequency range of 1~100MHz, and the curves of the real part μ′ and the imaginary part μ″ of the permeability as a function of frequency were obtained.

[0049] Example 9 R2Fe was prepared under the ball milling condition of 140 r / min as described in Example 6. 17 C x Soft magnetic powder was used as a magnetic filler and then subjected to SiO2 insulating coating treatment. The ball-milled R2Fe... 17 C x Soft magnetic powder undergoes surface insulation treatment to form a SiO2 insulating coating layer on the surface of the powder particles. This SiO2 insulating coating layer can be formed using the sol-gel method, wet chemical deposition, or other inorganic insulating coating methods. After coating, the powder is dried and sieved to obtain R2Fe with a SiO2 insulating layer on its surface. 17 C x Composite soft magnetic powder.

[0050] The obtained SiO2 is coated with R2Fe 17 C x Soft magnetic powder and silicone resin were mixed at a mass ratio of 90:10, thoroughly stirred and dispersed, pressed, and then cured to obtain R2Fe. 17 C x / SiO2 / resin-based soft magnetic composite samples were then tested using an impedance analyzer or vector network analyzer in the frequency range of 1–100 MHz to obtain the real part μ′ of the permeability, the imaginary part μ″ of the permeability, and the magnetic loss factor tanδ. μ And the curve of volume loss Pcv as a function of frequency.

[0051] Performance Evaluation Figure 2 Y2Fe obtained in Example 1 17 C 1.6 The orientation characteristics of the samples are characterized, among which Figure 2 (a) shows the X-ray diffraction patterns of the sample before and after orientation. Figure 2(b) shows the initial magnetization curves in the in-plane and out-of-plane directions. It can be seen that the sample exhibits a distinct preferred orientation after magnetic field orientation, indicating that the powder can align along the easily magnetized direction under the influence of an applied magnetic field. Figure 2 (b) It can be seen that magnetic saturation is more easily achieved in the in-plane direction than in the out-of-plane direction, exhibiting typical easy-plane magnetization characteristics, indicating that the R2Fe prepared in this invention... 17 C x Soft magnetic powders possess magnetocrystalline anisotropy characteristics that differ from traditional free-axis soft magnetic materials such as FeSi and FeSiAl, providing a basis for maintaining good magnetic response under high-frequency conditions.

[0052] Figure 3 The structural characterization results of the sample obtained in Example 2 are shown below. Figure 3 (a) shows the X-ray diffraction patterns of samples with different carbon contents. Figure 3 (b) and Figure 3 (c) shows the relationship between lattice parameters a and c and carbon content, respectively. It can be seen that all samples formed Th₂Ni. 17 The main phase structure was intact, and no obvious impurity phases were found, indicating that the introduction of interstitial carbon did not disrupt R2Fe. 17 The parent crystal structure. With increasing carbon content, all diffraction peaks shift slightly towards lower angles, while the lattice parameter 'a' gradually increases, and the lattice parameter 'c' changes relatively little. This indicates that carbon atoms preferentially occupy R₂Fe. 17 The interstitial positions of the crystal lattice cause lattice expansion in the basal plane direction. Due to the large radius of carbon atoms, their entry into the lattice increases the Fe-Fe atomic spacing, altering the local electronic environment and exchange interactions, thus providing a structural basis for subsequent improvements in magnetic properties.

[0053] Figure 4 The results show the Curie temperature variation of the sample obtained in Example 2. It can be seen that the Curie temperature of the material gradually increases with increasing carbon content. This is because interstitial carbon causes lattice expansion, bringing the Fe-Fe atomic spacing closer to the range favorable for ferromagnetic exchange interactions, thereby enhancing the exchange coupling between 3d electrons and ultimately leading to a significant increase in the Curie temperature. Furthermore, compared to interstitial nitrogen atoms, carbon exhibits better thermal stability during high-temperature heat treatment and is less prone to escaping, thus maintaining a stable lattice structure and magnetic properties over a long period.

[0054] Figure 5 The image shows the hysteresis loop of the sample obtained in Example 2. It can be seen that as the carbon content increases, the saturation magnetization of the material gradually increases, while the coercivity remains at a low level. This indicates that interstitial carbon modulation can further improve the overall soft magnetic properties of the material while maintaining excellent soft magnetic characteristics. This is mainly due to the interstitial carbon entering R2Fe. 17After lattice formation, lattice expansion is induced, altering the local electronic environment around Fe atoms. This enhances the exchange coupling between Fe atoms, increases the average magnetic moment of Fe atoms, and thus results in higher saturation magnetization. Simultaneously, interstitial carbon doping does not significantly increase the magnetic anisotropy of the material; therefore, the coercivity remains at a low level, which is beneficial for its application in high-frequency soft magnetic devices.

[0055] Table 1 presents the performance parameters of saturation magnetization and coercivity of the samples obtained in Example 2. It can be seen that as the carbon content increases, the saturation magnetization of the material gradually increases, while the coercivity changes relatively little. When the carbon content continues to increase, the increase in saturation magnetization tends to level off. This is because the interstitial positions in the lattice gradually become saturated, and further increasing the carbon content has limited effect on improving the lattice structure and exchange interactions. Therefore, there exists an optimal range for interstitial carbon content.

[0056] Table 1. Saturation magnetization and coercivity of the samples obtained in Example 2 Figure 6 The following are the structural and magnetic property characterization results of the series of samples with different rare earth elements obtained in Example 3, wherein... Figure 6 (a) is Y2Fe 17 C 1.6 Nd2Fe 17 C 1.6 and Pr2Fe 17 C 1.6 X-ray diffraction pattern of the sample, Figure 6 (b) shows the hysteresis loop of the corresponding sample. It can be seen that different rare earth element systems can all form stable Th₂Ni. 17 The main phase structure was intact, and no obvious impurity phases were found, indicating that interstitial carbon modulation does not disrupt R2Fe. 17 The parent crystal structure exhibits good system applicability. Due to differences in atomic radii and electronic structures among different rare earth elements, the lattice parameters and magnetic properties of each system vary to some extent, but all maintain significant ferromagnetic characteristics and low coercivity, indicating that the interstitial carbon modulation strategy proposed in this invention can effectively improve the performance of different R2Fe... 17 The soft magnetic properties of the base materials were investigated. In the Y system, due to the absence of 4f electron magnetic moment contributions, the magnetic properties were primarily determined by Fe-Fe exchange interactions. The Nd and Pr systems, influenced by the exchange coupling between rare-earth 4f electrons and Fe 3d electrons, maintained high saturation magnetization. These results demonstrate that the interstitial carbon modulation method proposed in this invention is applicable not only to Y₂Fe 17 The same applies to the system of Nd2Fe. 17 Pr2Fe 17 Various R2Fe 17 The base material has good system universality.

[0057] Figure 7 The following are the structural and magnetic properties characterization results of samples with different rare earth excess ratios obtained in Example 4, wherein... Figure 7 (a) X-ray diffraction patterns of samples with different rare earth excess ratios. Figure 7 (b) shows the hysteresis loop of the corresponding sample. It can be seen that, with changes in the excess rare earth element ratio, the samples all maintain Th2Ni... 17 The main phase structure is of the same type, but the purity of the main phase varies. When the excess proportion of rare earth elements is low, the actual ratio deviates from the stoichiometric ratio due to the easy volatilization of rare earth elements during the smelting process, resulting in the formation of a small amount of iron-rich impurities such as α-Fe. Appropriately increasing the excess proportion of rare earth elements can effectively compensate for the volatilization loss of rare earth elements during the smelting process and promote the formation of Th2Ni. 17 The formation of the main phase improves the phase purity of the material. Figure 7 (b) It can be seen that as the purity of the main phase increases, the saturation magnetization of the material further increases while maintaining a low coercivity. When the excess rare earth ratio continues to increase, the excess rare earth is difficult to completely dissolve in the main phase lattice, easily forming a rare earth-rich phase or producing a non-magnetic dilution effect, thus causing the increase in saturation magnetization to slow down or even decrease slightly. Therefore, considering the phase composition and magnetic properties, this invention determines that an 18% excess rare earth ratio is the optimal process parameter.

[0058] Figure 8 The images show X-ray diffraction patterns of samples obtained at different annealing temperatures in Example 5. It can be seen that the annealing temperature significantly affects the performance of Pr₂Fe₃. 17 C 1.6 The phase formation of the material is significantly affected. For some rare earth element systems, a small amount of impurity phases still exist after annealing at 1000 °C, indicating that due to the atomic radius and diffusion ability of rare earth elements, the solid-phase diffusion at this temperature is insufficient, and Th2Ni cannot be completely formed. 17 The main phase is Th2Ni. As the annealing temperature is increased to 1050 °C, stable Th2Ni phases are obtained in all systems. 17 The presence of a typical main phase structure indicates that increasing the annealing temperature promotes element diffusion and complete reaction, thereby improving the phase purity and structural stability of the material. Therefore, this invention determines 1050 °C as the optimal annealing temperature.

[0059] Figure 9 The microstructure and magnetic properties of the samples obtained at different ball milling speeds in Example 6 are shown below. Figure 9 (a) Scanning electron microscope images of samples at different ball milling speeds. Figure 9(b) shows the hysteresis loop of the corresponding sample. It can be seen that different ball milling speeds can break the annealed bulk alloy into micron-sized soft magnetic powder. As the ball milling speed increases from 100 r / min to 140 r / min, the powder particles become significantly finer, and the particle size distribution becomes more uniform; further increasing to 200 r / min, the reduction in powder particle size is limited. Figure 9 (b) It can be seen that the sample obtained by ball milling at 140 r / min maintained a high saturation magnetization and a low coercivity, exhibiting the best overall soft magnetic properties. When the ball milling speed was increased to 200 r / min, the material's coercivity increased significantly. This is mainly because excessively high ball milling energy subjectes the powder to stronger mechanical impact, easily introducing structural defects such as dislocations, lattice distortions, and residual stresses, increasing the resistance to domain wall movement, thereby improving the material's coercivity. Therefore, a moderate ball milling speed can effectively achieve the pulverization of bulk materials while avoiding the adverse effects of excessive ball milling on soft magnetic properties. Considering both powder refinement and magnetic properties, this invention adopts 140 r / min as the optimal ball milling speed.

[0060] Figure 10 The gas-atomized spherical R2Fe obtained in Example 7 17 C x The microstructure and magnetic properties characterization results of soft magnetic powder, among which... Figure 10 (a) is a scanning electron microscope image of spherical powder. Figure 10 (b) shows the hysteresis loop of the corresponding powder. It can be seen that R2Fe prepared using the gas atomization process... 17 C x The powder exhibits high sphericity, uniform size distribution, and a smooth surface without obvious cracks, providing a good powder foundation for subsequent insulating coating and pressing molding to prepare magnetic powder cores. Figure 10 (b) It can be seen that the gas-atomized powder still maintains a high saturation magnetization and a low coercivity, indicating that the gas atomization process can obtain R2Fe with both good sphericity and excellent soft magnetic properties. 17 C x Spherical powder provides a suitable powder raw material for the subsequent preparation of SMC magnetic powder cores. This indicates that the interstitial carbon control method proposed in this invention is not only applicable to irregular soft magnetic powders prepared by mechanical ball milling, but also to spherical soft magnetic powders prepared by gas atomization. It can meet the comprehensive requirements of soft magnetic composite magnetic powder cores for high sphericity, high flowability, and excellent soft magnetic properties, providing a basis for R2Fe... 17 C x The material provides a new preparation method for engineering applications in high-frequency power inductors and magnetic powder cores.

[0061] Figure 11 R2Fe obtained in Example 8 17 C xHigh-frequency permeability test results of polyurethane soft magnetic composite materials, among which Figure 11 (a) shows the curves of the real part μ′ and the imaginary part μ″ of the complex permeability as a function of frequency. Figure 11 (b) is the magnetic loss factor tanδ μ The curves show the change in permeability with frequency. It can be seen that the obtained composite material exhibits a significant permeability response in the frequency range of 1–100 MHz, and μ′ remains relatively stable over a wide frequency range, indicating that the ball-milled R2Fe… 17 C x The soft magnetic powder, after being composited with polyurethane, still maintains an effective high-frequency soft magnetic response. Meanwhile, μ″ and tanδ... μ The low levels observed across most of the test frequency bands indicate that this composite system possesses low magnetic loss potential. These results further demonstrate that the R2Fe prepared in this invention... 17 C x Soft magnetic powder not only has high saturation magnetization, low coercivity and high Curie temperature, but can also be further constructed into resin-based soft magnetic composite materials, which can be used in high-frequency power inductors, magnetic powder cores and other high-frequency soft magnetic devices.

[0062] Figure 12 The SiO2-coated R2Fe obtained in Example 9 17 C x The high-frequency magnetic properties test results of the resin-based soft magnetic composite sample, among which... Figure 12 (a) shows the curves of the real part μ' and imaginary part μ'' of the complex permeability as a function of frequency. Figure 12 (b) is the magnetic loss factor tanδ μ Curve of frequency variation Figure 12 (c) shows the loss test results of the composite sample. It can be seen that the R2Fe coated with SiO2... 17 C x The resin-based soft magnetic composite sample exhibits a significant permeability response in the MHz band, and μ' remains relatively stable over a wide frequency range, indicating that after insulating coating and resin composite, R2Fe... 17 C x The powder still provides an effective soft magnetic response. Meanwhile, μ'' and tanδ... μ The overall low level indicates that the SiO2 insulating coating layer can effectively reduce interparticle conductive losses and high-frequency eddy current losses. Loss test results further demonstrate that the composite sample possesses usable low-loss characteristics under a high-frequency alternating magnetic field. These results prove that the R2Fe obtained in this invention... 17 C xSoft magnetic powder can be further prepared into high-frequency, low-loss soft magnetic composite materials through SiO2 insulation coating and resin bonding molding, which can be used in high-frequency power inductors, magnetic powder cores and other high-frequency soft magnetic devices.

[0063] In summary, this invention proposes an R2Fe based on interstitial carbon modulation. 17 C x This paper describes a soft magnetic powder material and its preparation method. Fe-C pre-alloying is used as a stable carbon source, allowing carbon atoms to be dissolved in R₂Fe in an interstitial form. 17 The lattice maintains Th2Ni 17 While maintaining a stable main phase structure, this invention achieves lattice parameter tuning, enhances Fe-Fe exchange interactions, thereby increasing the Curie temperature and saturation magnetization of the material while maintaining low coercivity. Furthermore, this invention combines rare earth compensation, homogenization annealing, and powder preparation processes to further improve the main phase purity, microstructure uniformity, and overall magnetic properties of the material. Specifically, an 18% rare earth excess and a homogenization annealing temperature of 1050 °C are beneficial for obtaining stable Th₂Ni. 17 The main phase structure is [not specified]. To meet different application requirements, this invention can prepare micron-sized soft magnetic powder suitable for magnetic powder cores using mechanical ball milling, or high-sphericity soft magnetic powder using gas atomization. Specifically, under mechanical ball milling conditions, the powder prepared at 140 r / min possesses both fine particle size and excellent soft magnetic properties; the spherical powder obtained by gas atomization exhibits good sphericity, flowability, and pressing performance, providing excellent powder raw materials for subsequent insulating coating and magnetic powder core preparation. Furthermore, this invention utilizes uncoated R2Fe [not specified]... 17 C x Powder / resin composite samples and SiO2-coated R2Fe 17 C x High-frequency permeability and loss tests on powder / resin composite samples verified the effective magnetic response and low-loss application potential of this type of powder in resin-based soft magnetic composite materials. This demonstrates that the present invention not only provides an R2Fe... 17 C x This invention discloses soft magnetic powder materials and their preparation methods, and also provides application pathways for them in insulating coating, resin composite molding, and high-frequency magnetic powder cores. Compared with the FeSi, FeSiAl, FeNi, and amorphous and nanocrystalline easily-magnetized metal soft magnetic powders used in existing SMCs, this invention uses the easily-magnetized material R2Fe. 17 As a soft magnetic powder system, the base material has better high-frequency magnetic response potential while maintaining high saturation magnetization and high Curie temperature. It can provide a new material design idea for overcoming the limitation of the decrease in magnetic permeability of traditional free-axis metal soft magnetic materials under high-frequency conditions.

[0064] Furthermore, the interstitial carbon regulation method proposed in this invention has good system applicability and is applicable not only to Y2Fe. 17 The same applies to the system of Nd2Fe. 17 Pr2Fe 17 Various R2Fe 17 This base material can provide a new technical route for the composition design and performance optimization of high-frequency soft magnetic powder materials. The obtained R2Fe 17 C x Soft magnetic powder can be used as a magnetic powder in soft magnetic composite materials (SMC) for high-frequency magnetic devices such as high-frequency power inductors, providing a new material option for the development of high-frequency, low-loss, and high-power-density soft magnetic devices.

Claims

1. An easy-faceted R2Fe for high-frequency soft magnetic composite material applications 17 C x Rare earth alloy soft magnetic powder, wherein R is any one of Y, Nd, or Pr, and x is 0.5~3.2; the soft magnetic powder has Th2Ni 17 It has a main phase structure and exhibits easy-faceted magnetocrystalline anisotropy.

2. The soft magnetic powder according to claim 1, characterized in that, x is between 1.6 and 2.

2.

3. The soft magnetic powder according to claim 1, characterized in that, R is Y.

4. A high-frequency soft magnetic composite material, comprising a magnetic phase and an insulating coating layer covering the surface of the magnetic phase, characterized in that, The magnetic phase is the soft magnetic powder according to any one of claims 1 to 3.

5. The high-frequency soft magnetic composite material according to claim 4, characterized in that, The insulating coating layer is a SiO2 insulating coating layer and / or an organic resin adhesive layer.

6. A method for preparing the soft magnetic powder according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Raw material preparation: according to the chemical formula R2Fe 17 C x The ingredients are prepared by using Fe-C pre-alloying as a carbon source to introduce carbon elements, with rare earth elements in excess of 10% to 25%. (2) Alloy smelting: The prepared raw materials are smelted under a protective atmosphere, and the smelting is repeated no less than 3 times to obtain R2Fe. 17 C x Alloy ingots; (3) Homogenization annealing: The obtained ingot is annealed at 1000~1050℃ and then cooled; (4) Powder preparation: The annealed alloy is crushed and ball-milled using a planetary ball mill with a ball-to-material ratio of 15:1 to 25:1 and a ball-milling time of 0.5 to 2 hours to obtain the soft magnetic powder.

7. The preparation method according to claim 6, characterized in that, The excess ratio of rare earth elements is 18%.

8. The preparation method according to claim 6, characterized in that, The annealing temperature is 1050℃.

9. The preparation method according to claim 6, characterized in that, The ball milling speed is 140 r / min; or, in step (4), a vacuum atomization process is used instead of the ball milling process to prepare spherical soft magnetic powder.

10. The use of the soft magnetic powder according to any one of claims 1 to 3 in the preparation of high-frequency power inductors, high-frequency magnetic powder cores or high-frequency soft magnetic devices.